Clinical presentation of peritoneal tuberculosis. Issue 2 (4th March 2023) - Ozturk, Nazli Begum; Tsagkaris, Christos; Dolek, Naile; Iliaz, Raim
Abstract: Peritoneal tuberculosis arises from hematogenous spread of pulmonary foci or from direct spread from an adjacent structure. Diagnosis of peritoneal tuberculosis can be challenging due to nonspecific symptoms, insidious onset, and variable imaging findings. Herein, we report a patient presenting with ascites who was eventually diagnosed with peritoneal tuberculosis.